Deletion of protein tyrosine phosphatase 1B in hepatocytes attenuates inflammation, steatosis, and fibrosis in a dietary mouse model of metabolic dysfunction-associated steatohepatitis - Ming-Fo Hsu; Yoshihiro Ito; Ulrik Mjaaseth; James Graham; Peter J. Havel; Fawaz G. Haj (Molecular Medicine, 2026)
Abstract Background Metabolic dysfunction-associated steatohepatitis (MASH) is a leading cause of liver-related morbidity and mortality. The current interventions are limited, underscoring the need for novel mechanism-based therapies. Protein tyrosine phosphatase 1B (PTP1B) regulates phosphotyrosine signaling and hepatic metabolism, but its role in MASH remains incompletely understood. Methods To elucidate the impact of modulating PTP1B expression in MASH, we used mice with hepatocyte-specific PTP1B disruption in the fast-food diet (FFD) model of the disease and then monitored alterations in inflammation, steatosis, and fibrosis. Results In this study, we observed elevated hepatic PTP1B expression in the FFD mouse model of MASH and in liver biopsies from MASH patients. PTP1B deficiency ameliorated FFD-induced hepatic injury and inflammation as evidenced by lower alanine aminotransferase, Tnf and Il1b, and NFκB phosphorylation. Additionally, PTP1B deficiency partially rebalanced the hepatic and systemic lipid dysregulation under the FFD-fed state. Notably, PTP1B deficiency alleviated the hepatic fibrosis induced by the prolonged FFD regimen. Moreover, mice with hepatic PTP1B deficiency exhibited improved glucose control under FFD independently of body weight changes. Mechanistically, PTP1B deficiency was associated with enhanced hepatic insulin signaling and decreased oxidative stress. Conclusions Collectively, these findings establish that PTP1B deficiency in hepatocytes modulates several pathways implicated in MASH and confers improvements that may curtail disease progression. Further investigation is warranted into targeting this phosphatase as part of the armamentarium in the therapeutic landscape for MASH.